ND, SR, PB, O ISOTOPE CHARACTERISTICS OF TWO TYPES GRANITES IN THE SAWUER REGION, XINJIANG - Yuan F.; Zhou T.; Fan Y.; Tan L.; Yue S.; Yang W.; He L. (My University, 2006)
The Sentasi and the Wokensala intrusions are I type granites in west Zhungeer Sawuer region, Xinjiang. They are the partial alkali rocks and formed at the late of Early Carboniferous in the extendable period or compressible to extendable period of the post-collisional phase. The Kuoyitasi and the Qiaqihai intrusions are A2-type granites. They formed at the beginning of Early Permian during the extendable period of the post-collisional phase. The Nd, Sr, Pb isotope characteristics of I type granites are similar to those of A type granites. The I type and A type granites came from the mantle magma. They were the results of different evolutive phase of the same source magma. The O isotope and the REE characteristics of I type and A type granites were different distinctly. The I type and A type granites from mantle sources formed at late Palaeozoic in west Zhungeer Sawuer region can further confirm the vertical addition of the continental crust. The A type granites in west Zhungeer Sawuer region can belong to the Ulungur alkali granites belt in east Zhungeer.
Keywords: GRANITE; ISOTOPE; POST-COLLISIONAL; SAWUER REGION; XINJIANG; Палеозой::Пермская; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous